Malaysian and Italian trend line for Covid-19: A study on trend analysis - Wan Ahmad, Wan Muhammad Amir bin; Ibrahim, Noor Azlinaliana; Nawi, Mohamad Arif Awang; Mohd Noor, Nor Farid; Mohamad, Noraini; Aleng, Nor Azlida; Mohamad Ghazali, Farah Muna; Um Min Allah, Nasar (Universitas Ahmad Dahlan, 2021)
The first objective of this study was to evaluate trend line pattern, obtain the appropriate statistical equation model, and predict individual numbers infected by Covid-19. The second objective is to obtain a predictive equation model and forecast death rate for Malaysia and Italy. Malaysia's first positive case Covid-19 recorded January 24, 2020, consisting of three cases. Collected from January 24 to March 29, 2020. Sixty-six day-observations, based on their trend line pattern, earned special attention. Although the first positive case was identified on January 31, 2020, involving two patients. From January 31 to March 29, 2020, approximately 59 observations were collected from Italy. On 18 March 2020, the pattern will contrast with the Malaysian Movement Control Order (MCO). Malaysia and Italy collect death figures. A similar methodology will be applied to find the best-fitted model that fits both countries' death-number scenario. In Italy, the number of Covid-19-infected patients rises and meets quadratic trend line patterns. This induces extreme public distress and diversion. The quadratic trend line series analysed individual Covid-19-infected results. After March 18, 2020, it will continue to use a linear pattern. However, trend deaths also follow quadratic trend line pattern. Trend-line quadratic matched Italy's results. The quadratic line-of-trend model projection demonstrated dominance in estimating infected Covid-19. The quadratic death line from daily death collection data also showed superiority in estimating death number. The fitted quadratic model is better fitted in the Malaysian case, but the pattern shifts to linear trend line after MCO is implemented.